Comparative Effect Of Standard Balance Exercises And Progressive Resistance Strength Training On Balance In Patients With Diabetic Neuropathy. - Revilla, Jahnavi; Doijad, Amruta (Journal of Neonatal Surgery, 2025)
Introduction- Diabetic nerve dysfunction is a common adverse effect associated with type 2 diabetes mellitus (T2DM) that affects postural instability leading to a higher risk of falling. Balance impairment in diabetic neuropathy patients involves interventions to improve postural control. This research aims to determine the effectiveness of standard balance exercises and progressive resistance training in enhancing balance in in diabetic neuropathy patients. Methodology- This interventional study used simple random sampling method to allocate participants into two intervention groups. A total of 48 participants (Group A =24; Group B=24) meeting the inclusion criteria of all genders aged 50-65 years with berg balance score of 20-44 and type 2 diabetes mellitus duration of 5-10 years, will be recruited. Group A received standard balance exercises and group B underwent progressive strength training following the Delorme and Watkins protocol. Both interventions conducted four sessions per week for a duration of four weeks. Baseline and post interventions assessments had taken using the balance measures such as the Berg Balance Scale and Timed Up and Go test. Results- According to this study, both therapies showed marked enhancement in postural stability, demonstrated by reduced TUG durations and elevated BBS values. (Group A) BBS increased from 36.04 to 39.79 (p < 0.0001) and TUG decreased from 22.92 to 20.29 (p < 0.0001). (Group B) BBS improved from 36.50 to 40.58 (p < 0.0001) and TUG from 23.04 to 20.42 (p < 0.0001). Although Group B showed slightly better outcomes. Conclusion- Patients with diabetic neuropathy can improve their balance with both resistance and balance exercises. Although there may be a little more benefit from progressive resistance training, both strategies are beneficial and may be customized for each patient's needs